Illusionism, sleight of hand, ventriloquism and circus in Costa Rica (1941-1971) - Urbina Gaitán, Chester (2025)
This article studies the importance of illusionism, sleight of hand, ventriloquism and circus shows in Costa Rica during the years from 1941 to 1971, in free time and in the process of cultural interaction of national social groups, mainly capitalians. For this purpose, a compilation was made from journalistic sources of the time of publications relating to the names of the artistic companies and artistic acts or numbers, places of presentation, names of artists and animals that were exhibited. The aforementioned shows were exhibited mainly in San José, so they were not witnessed in much of the country. Likewise, they had to compete with other amusements and entertainment that attracted the attention of the vallecentralino public such as soccer, theater and cinema.The time period analyzed goes from 1941 to the founding of the Ministry of Culture, Youth and Sports in 1971.